The impact of out-of-hospital models of care on paediatric emergency department presentations. Issue 2 (26th October 2017) - Viner, Russell M; Blackburn, Frances; White, Francesca; Mannie, Randy; Parr, Tracy; Nelson, Sara; Lemer, Claire; Riddell, Anna; Watson, Mando; Cleugh, Francesca; Heys, Michelle; Hargreaves, Dougal S
Abstract : Objective: To estimate the potential impact of enhanced primary care and new out-of-hospital models (OOHMs) on emergency department (ED) presentations by children and young people (CYP). Design: Observational study. Patients & setting: Data collected prospectively on 3020 CYP 0–17.9 years from 6 London EDs during 14 days by 25 supernumerary clinicians. CYP with transient acute illness, exacerbation of long-term condition (LTC), complex LTC/disability and injury/trauma were considered manageable within OOHM. OOHMs assessed included nurse-led services, multispecialty community provider (MCP), primary and acute care system (PACS) plus current and enhanced primary care. Measures: Diagnosis, severity; record of investigations, management and outcome that occurred; objective assessment of clinical need and potential alternative management options/destinations. Results: Of the patients 95.6% had diagnoses appropriate for OOHM. Most presentations required assessment by a clinician with skills in assessing illness (39.6%) or injuries (30.9%). One thousand two hundred and ninety-one (42.75%) required no investigations and 1007 (33.3%) were provided only with reassurance. Of the presentations 42.2% were judged to have been totally avoidable if the family had had better health education. Of the patients 26.1% were judged appropriate for current primary care (community pharmacy or general practice) with 31.5% appropriate for the combination of enhanced general practice and community pharmacy. Proportions suitable for new models were 14.1% for the nurse-led acute illness team, MCP 25.7%, GP federation CYP service 44.6%, comprehensive walk-in centre for CYP 64.3% and 75.5% for a PACS. Conclusions: High proportions of ED presentations by CYP could potentially be managed in new OOHMs or by enhancement of existing primary care.